Agitation-dependent biomechanical forces modulate GPVI receptor expression and platelet adhesion capacity during storage - Ehteramolsadat Hosseini; Amin Solouki; Masood Haghshenas; Mehran Ghasemzadeh; Simone M. Schoenwaelder (Thrombosis Journal, 2022)
Abstract Background Continuous agitation during storage slows down the platelet storage lesions. However, in special circumstances, manual-mixing can be alternatively used to store products for short time periods without compromising platelet quality. Based on this finding, and given the role of shear stress in modulating receptor expression, we were interested in comparing the levels of platelet adhesion receptor, GPVI and platelet adhesion capacity under each storage condition. Methods Platelet concentrates (PCs) were divided into three groups: continuously-agitated PCs (CAG-PCs) with or without PP2 (Src kinase inhibitor) and manually-mixed PCs (MM-PCs). Platelet count/MPV, swirling, GPVI and P-selectin expression, GPVI shedding, platelet adhesion/spreading to collagen were examined during 5 days of storage. Results While MM- and CAG-PCs showed similar levels of P-selectin expression, GPVI expression was significantly elevated in MM-PCs with lower GPVI shedding/expression ratios, enhanced platelet adhesion/spreading and swirling in manually-mixed PCs. Of note, CAG-PCs treated with PP2 also demonstrated lower P-selectin expression and GPVI shedding, higher GPVI expression and attenuated swirling and spreading capability. Conclusion Given the comparable platelet activation state in MM and CAG-PCs as indicated by P-selectin expression, enhanced platelet adhesion/spreading in MM-PCs, along with relatively higher GPVI expression here, supports previous studies demonstrating a role for biomechanical forces in modulating GPVI-dependent function. Thus, lower GPVI expression in CAG-PCs may be due to shear forces induced by agitation, which keeps this receptor down-regulated while also attenuating platelet adhesion/spreading capacities during storage. Low platelet function in PP2-CAG-PCs also highlights the importance of Src-kinases threshold activity in maintaining platelets quality.